DOI: 10.26686/wgtn.17145899.v1
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards the realization of an optical Far-Field Superlens

Abstract: <p>Conventional optics suffer from a fundamental resolution limit due to the nature of light. The near-field superlens concept was introduced two decades ago, and its theory for enabling high resolution imaging is well-established now. Initially, this superlens, which has a simple setup, became a hot topic given the proposition of overcoming the diffraction limit. It has been demonstrated that a near-field superlens can reconstruct images using evanescent waves emanating from small objects by means of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 239 publications
(324 reference statements)
0
0
0
Order By: Relevance
“…Progress has also been made towards the realisation of an FSL with a 2D diffraction grating. Using a 2D diffraction grating that allows spatial frequencies in multiple directions to be acquired has been proposed [83,84]. Figure 2.11b illustrates the concept, where the k x and k y spatial frequencies are transformed into the propagating band.…”
Section: The Far-field Superlensmentioning
confidence: 99%
See 4 more Smart Citations
“…Progress has also been made towards the realisation of an FSL with a 2D diffraction grating. Using a 2D diffraction grating that allows spatial frequencies in multiple directions to be acquired has been proposed [83,84]. Figure 2.11b illustrates the concept, where the k x and k y spatial frequencies are transformed into the propagating band.…”
Section: The Far-field Superlensmentioning
confidence: 99%
“…Figure 2.11b illustrates the concept, where the k x and k y spatial frequencies are transformed into the propagating band. Electromagnetics finite element modelling (FEM) has been conducted, which suggested that by adjusting the illumination polarisation and using a 2D grating design, spatial features in the xand ydirection could be recovered in the far-field [84]. The proposed 2D FSL was illuminated by 365 nm wavelength light.…”
Section: The Far-field Superlensmentioning
confidence: 99%
See 3 more Smart Citations